Q: 4p plus 9 plus -7p plus 2 equals?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

4p + 9 - 7p + 2 4p - 7p + 9 + 2 p(4 - 7) + 9 + 2 -3p + 11

4p + 9 + (-7p) + 2 = 4p - 7p + 9 + 2 = -3p + 11

Collect like terms together: 4p + 9 + 7p + 2 = (4p + 7p) + (9 + 2) = (4 + 7)p + 11 = 11p + 11 = 11(p + 1)

7p + 2 = 5p + 8 7p - 5p = 8 - 2 2p = 6 p = 3

If you mean: 7p-3p+4-2 = 2p-1+10 => 4p+2 = 2p+9 => 2p = 7 Therefore: p = 7/2 => p = 3.5

Related questions

4p + 9 - 7p + 2 4p - 7p + 9 + 2 p(4 - 7) + 9 + 2 -3p + 11

4p + 9 + (-7p) + 2 = 4p - 7p + 9 + 2 = -3p + 11

11p+11

Collect like terms together: 4p + 9 + 7p + 2 = (4p + 7p) + (9 + 2) = (4 + 7)p + 11 = 11p + 11 = 11(p + 1)

It is: 11p+11 simplified

7p + 2 = 5p + 8 7p - 5p = 8 - 2 2p = 6 p = 3

4p+2 = 3p-7 4p-3p = -7-2 p = -9

If you mean: 7p-3p+4-2 = 2p-1+10 => 4p+2 = 2p+9 => 2p = 7 Therefore: p = 7/2 => p = 3.5

p = -1

8p+2=4p-10 8p-4p=-2-10 4p=-12 p=-12/4 =-3

If 3p-5=9-4pthen 3p+4p=9+5=14then 7p=14and p=14/7so p=2Proof:(3 x 2)-5=19-(4 x 2)=1

4p + 6 = 2 4p = -4 (subtracting 6 from both sides) p = -1 (dividing both sides by 4)